Did Calvinists Have a Guilt Complex? Reformed Religion, Conscience and Regulation in Early Modern Europe - Murdock, Graeme (Studies in church history, 2004)
This essay assesses ideas and evidence about the response of Calvinists to sin during the Early Modern period. It takes as a starting-point the analysis provided by Max Weber about the development of Reformed salvation theology in later Calvinism. Weber suggested that Calvinists came to connect the eternal fate of their souls with their behaviour on earth, and attempted to exert systematic controls over their own conduct. Calvinists, Weber argued, developed a mind-set of methodical self-analysis and exhibited constant vigilance, concern and guilt about ongoing sin. Some early modern Calvinists certainly did demonstrate this highly refined personal anxiety about their wrong-doing, and worried about what their lack of enthusiasm and commitment to true religion and moral conduct might mean. However, most Reformed ministers across the Continent seem to have been rather more concerned that members of their congregations did not feel guilty enough about their sins, and alongside encouraging self-discipline through sermons and catechizing, turned to elders and, where possible, to state authorities, to enforce high standards of morality on often recalcitrant parishioners.